2014
DOI: 10.1002/chem.201402499
|View full text |Cite
|
Sign up to set email alerts
|

Hydride‐Rhodium(III)‐N‐Heterocyclic Carbene Catalysts for Vinyl‐Selective H/D Exchange: A Structure–Activity Study

Abstract: A series of neutral and cationic Rh(III) -hydride and Rh(III) -ethyl complexes bearing a NHC ligand has been synthesized and evaluated as catalyst precursors for H/D exchange of styrene using CD(3)OD as a deuterium source. Various ligands have been examined in order to understand how the stereoelectronic properties can modulate the catalytic activity. Most of these complexes proved to be very active and selective in the vinylic H/D exchange, without deuteration at the aromatic positions, displaying very high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 120 publications
0
15
0
Order By: Relevance
“…In this context, inspired by studies from Bergman and Tilley, Hartwig described an iridium pincer complex, that allowed for the selective H/D scrambling at alkenyl moieties without isomerization, exploiting C 6 D 6 as the deuterium source . In contrast, Grotjahn showed that allylic deuteration of alkenes was accomplished by a bifunctional imidazolylphosphine,, whereas Oro used NHC‐supported rhodium(III) hydride catalyst for the selective β‐deuteration of styrenes ,. Furthermore, Jia and Lin exploited [RuHCl(CO)(PPh 3 ) 3 ] as the catalyst, while Nishimura and Yorimitsu recently used [Ir(OH) (cod)] 2 and N ‐mesylbenzamides to selectively label stilbenes…”
Section: Methodsmentioning
confidence: 99%
“…In this context, inspired by studies from Bergman and Tilley, Hartwig described an iridium pincer complex, that allowed for the selective H/D scrambling at alkenyl moieties without isomerization, exploiting C 6 D 6 as the deuterium source . In contrast, Grotjahn showed that allylic deuteration of alkenes was accomplished by a bifunctional imidazolylphosphine,, whereas Oro used NHC‐supported rhodium(III) hydride catalyst for the selective β‐deuteration of styrenes ,. Furthermore, Jia and Lin exploited [RuHCl(CO)(PPh 3 ) 3 ] as the catalyst, while Nishimura and Yorimitsu recently used [Ir(OH) (cod)] 2 and N ‐mesylbenzamides to selectively label stilbenes…”
Section: Methodsmentioning
confidence: 99%
“…Complementary to the work of Grotjahn (vide supra), Castarlenas and Oro reported a beautifully detailed method for the β-selective deuteration of styrenes (147→148) using Nheterocyclic carbene (NHC) and 8-quinolinol-derived ligands within catalysts, such as 146 (Scheme 45). [140,141] The reaction mechanism merits discussion, as detailed studies revealed the essential role played by all ligands bound to the Rh centre (Scheme 46). [141] Labeling heteroatom X-H bonds can deliver valuable intermediates en route to labeling more complex organic molecules.…”
Section: Rhodiummentioning
confidence: 99%
“…In 2011, Oro and co‐workers reported Rh(NHC)‐catalyzed highly mild and regioselective H/D exchange reactions at the β‐position of styrene derivatives . The 16‐electron rhodium(III) hydride catalyst was synthesized by the oxidative addition of the O−H bond of 8‐hydroxyquinoline to [Rh(IPr)(coe)Cl] 2 (coe= cis ‐cyclooctene), and the resulting hydride ligand is located at the apical position of the square planar rhodium complex (Scheme ).…”
Section: Reaction Involving Rhodium Hydride Speciesmentioning
confidence: 99%
“…Later, the same group reported more detailed studies on the NHC structure‐reactivity relationship in the rhodium system . A series of Rh‐NHC hydride species having different NHC ligands and other stabilizing ligands was synthesized and investigated in H/D exchange reactions (Scheme ).…”
Section: Reaction Involving Rhodium Hydride Speciesmentioning
confidence: 99%